2006
DOI: 10.1038/sj.jp.7211551
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence mesenteric artery blood flow velocity in newborn preterm infants

Abstract: Objectives: To identify demographic and clinical variables that relate to the postnatal increase in intestinal blood flow velocity in preterm infants.Study design: Fasting or preprandial peak systolic velocity (PSV) and time-averaged mean velocity (TAMV) in the superior mesenteric artery were measured once each day for the first 5 days of life. We investigated the relationship between blood flow velocity and the following variables: birth weight, gestational age, feeding volumes, number of days to reach full f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
3
24
1
1
Order By: Relevance
“…5 An additional finding of the present study is that the increase in SMA BFV from 0 to 30 min after feeding was greater when infants were on CPAP versus off CPAP. To our knowledge, these are the only reports of CPAP effects on intestinal blood flow velocity.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…5 An additional finding of the present study is that the increase in SMA BFV from 0 to 30 min after feeding was greater when infants were on CPAP versus off CPAP. To our knowledge, these are the only reports of CPAP effects on intestinal blood flow velocity.…”
Section: Discussionsupporting
confidence: 57%
“…5,[9][10][11][12][13][14][15] Other extrinsic factors that affect intestinal blood flow velocity in preterm infants include the type and volume of enteral feeding given, 10,13 -17 various pharmacologic agents 18,19 -21 and phototherapy. 22,23 Greater increases in postnatal and postprandial SMA BFV in preterm neonates are associated with less intestinal dysmotility 6 and with better tolerance to enteral feedings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly lower mesenteric tissue oxygenation was recorded in infants with a large PDA on NCPAP, but not in the mechanically ventilated neonates. Large transductal size and NCPAP, which is a known factor that influences mesenteric artery blood flow velocity in preterm infants, 29,30 is one possible explanation for this finding, although reduction in mesenteric blood flow does not always impair Regional tissue oxygenation in infants with PDA A Petrova et al mesenteric tissue oxygenation. 31 We did not find a decrease in mesenteric tissue oxygenation in infants with moderate PDA on NCPAP, maybe because of the inadequate number of observed cases with moderate PDA on CPAP (n ¼ 2).…”
Section: Discussionmentioning
confidence: 97%
“…Blood flow in the superior mesenteric artery is decreased in infants supported with NCPAP when compared with those off NCPAP. 11 This finding suggests that the blood velocity may not be adequate to support the tremendous intestinal growth that occurs soon after birth, leaving the intestine more vulnerable to developing NEC. On the other hand, experimental studies demonstrated mechanical ventilation to create a significant cascade of inflammation leading to severe capillary leak that is not limited to the lungs.…”
mentioning
confidence: 99%